PENGARUH TINGKAT KEKERINGAN TERHADAP PERTUMBUHAN GENERATIF KULTIVAR KACANG TUNGGAK (Vigna unguiculata L) - Zulifah Mahdalena (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
Small and medium industries including household businesses really need to be developed into businesses that are able to develop independently into businesses to increase community income. Household businesses built by the community must of course take into account the potential that can support business continuity. The study was conducted on household businesses Abon Ikan Tuna